2003
DOI: 10.5191/jiaee.2003.10109
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors and Employees’ Job Satisfaction in Large-Scale Private Farms in Ogun State, Nigeria

Abstract: The study assessed various motivating factors and level of job satisfaction of staff in large-scale private agricultural farms in Ogun State, Nigeria. A total of 90 employees from five purposively selected farms were surveyed using structured questionnaire for data collection. The findings of the study show that high remuneration, promotion, good pension scheme, job security and recognition of staff were rated as very important motivating factors. There was also no significant relationship between socio-econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 3 publications
3
5
2
2
Order By: Relevance
“…However, unlike the findings of Gaziouglu and Tanzal (2002) and Burke (1996), this study found no significant difference in job satisfaction based on positions held by employees in the banking industry. Again, the fact that no difference occurred in employees work motivation across their job position confirms the findings of Oloruntoba and Ajayi (2003) and Nandanwar et al (2010) that designation has no significant impact on employees' motivation. All the same, this finding contradicts the view of Furnham et al (n.d) that job status is a significant positive predictor of job security and conditions, and negative predictor of employees' reward and status.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…However, unlike the findings of Gaziouglu and Tanzal (2002) and Burke (1996), this study found no significant difference in job satisfaction based on positions held by employees in the banking industry. Again, the fact that no difference occurred in employees work motivation across their job position confirms the findings of Oloruntoba and Ajayi (2003) and Nandanwar et al (2010) that designation has no significant impact on employees' motivation. All the same, this finding contradicts the view of Furnham et al (n.d) that job status is a significant positive predictor of job security and conditions, and negative predictor of employees' reward and status.…”
Section: Discussionsupporting
confidence: 77%
“…However, Furnham et al further opined that age was not a significant predictor of status and rewards and personal development and security factor scores. Their findings corroborate Oloruntoba and Ajayi (2003)'s finding that there is no significant relationship between socioeconomic characteristics (e.g., age) of respondents and motivational factors. In the terms of the relationship between work motivation and job position, Oloruntoba and Ajayi (2003) in their study titled "Motivational factors and employees' job satisfaction in large-scale private farms in Ogun State, Nigeria" concluded that employees' motivation was not influenced by their respective designation.…”
Section: Job Satisfaction Work Motivation and Organisational Commitmentsupporting
confidence: 81%
See 3 more Smart Citations